ANALISIS GOOD CORPOTARE GOVERNANCE TERHADAP KINERJA KEUANGAN PERUSAHAAN (Studi Kasus Perusahaan Sektor Pertanian yang Terdaftar di Indeks Saham Syariah Bursa Efek Indonesia Tahun 2017 - 2021) - Ayu Puspitaningtyas (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2023)
This study aims to analyse the effect of corporate governance as measured by the variables of the proportion of institutional ownership and the proportion of independent members of the board of commissioners meeting on the company financial performance as measured by return on assets (ROA) and Â return on equity (ROE).The population used in this study is an agriculture company listed on the Indonesia Stock Exchange during 2017-2021. Sampling technique used in this research is purposive sampling method and obtained 30 samples. This study uses secondary data from annual reports obtained from Indonesia Stock Exchange (BEI) in the period 2017-2021. The method of analysis used to analyze data is multiple regression. Based on the results of hypothesis testing in this study, it is evident that (1) the proportion of institutional ownerships has a negative and significant effect on the ROA. (2) the proportion of independent members of the board of commissioners positively and significant affects the ROA. (3) the proportion of institutional ownerships has a negative and significant effect on the ROE. (4) the proportion of independent members of the board of commissioners positively and doesnâ€™t significant affects the ROE..